Model studies on the synthesis of the natural meroterpenoid cordiaquinone A - Batalini, Claudemir; Bieber, Lothar Wilhelm (Eclética Química, 2001)
Two main strategies for the synthesis of the natural meroterpenoid cordiaquinone A (1) - isolated of the roots of Cordia corymbosa G. Don (Boraginaceae) - were tested on model compounds. Whereas all attempts of alkylation of e-caprolactone (10) were unsuccessful, the coupling of epoxycitronellol (17) with an appropriate organocuprate proceeded in the expected direction.